The Merits and Drawbacks of Electronic Journals: A Research Survey of Aerospace Scientists and Engineers of Bangalore - Guruprasad, R. (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
Today, scientific journals undoubtedly represent the most vital means for disseminating research findings. Often, the research challenges common assumptions and/or the research data presented in the published scientific literature in order to gain a clearer understanding of the facts and findings. Depending upon the policies of a given journal, articles may include reports of original research, re-analyses of others’ research, reviews of the literature in a specific area, proposals of new but untested theories, or opinion pieces. One can also say that, journals are fundamental to formal scholarly communication. It is also observed that for more than three centuries, scholarly journals have played a pivotal role in the creation and dissemination of knowledge by serving as the primary medium of scholarly communication. This has however remained unchanged in form and function over its lifetime. It is now very clear that science as we know it is scarcely imaginable without the scholarly journal [1,2].A research study was undertaken to study the ‘Advantages and Disadvantages of Electronic Journals’ The geographic boundary of this research study consisted of 16 prominent aerospace organizations of Bangalore. The age-group of this study was between 21-60 years. The broad areas of specialization of the Aerospace Scientists and Engineers have been classified into (a) Thermal and Fluid Sciences, (b) Avionics, Guidance and Control, (c) Aerospace Structures and Allied Mechanical Sciences, (d) Materials and Metallurgy, (e) Flight Operations and other Allied Disciplines, and (f) General Engineering and Support Sciences. The major conclusions of this study are: (a) Analysis of Variance (ANOVA) was applied for testing the significant difference among the 16 mean scores attained from the scientists and engineers of the aerospace organizations for ‘Advantages of Use of e-Journals’. It is observed that all the 16 aerospace organizations show a significant difference (P < 0.05) in their mean scores viz., ‘Current / Up to Date Information’, Ease of Search’, Ease of Browsing’, Multi-User Access, Fast Access, ‘Ability to Download’, ’24 Hour Access’, ‘Available Before Print’, ‘Search-ability of Databases among Journals’, ‘e-Back Volumes are Available’, ‘Non-Availability of Print Volumes’, ‘Easy Backup Availability’ and ‘Multiple e-Choice of Formats (PDF, RTF, DOC and HTML)’. (b) Analysis of Variance (ANOVA) was applied for testing the significant difference among the 16 mean scores attained from the scientists and engineers of the aerospace organizations for ‘Disadvantages of e-Journals’. It is observed that all the 16 aerospace organizations show a significant difference (P < 0.05) in their mean scores viz., ‘Slow Downloads’, ‘Additional Payment’, ‘Problems with Print Facilities in Databases’, ‘Dependence on Connectivity’,‘QualityofPrintImagesisLow’and‘ItisDifficulttoReadonScreen,exceptfor‘Frames’,‘Navigation’, ‘Insecurity of Preservation’ and ‘Accessibility’